ADDITION OF TEMPE AND OLD FERMENTATION TO THE QUALITY OF ALBUMIN FLOUR EGG - Mhd. Iqbal Nusa; Budi Suarti; Rahman Ali Marbun (AGRIUM: Jurnal Ilmu Pertanian, 2017)
This study aimed to determine the effect of tempe yeast in the fermentation process of the nature quail egg albumin quality flour quail egg albumin. This study uses a completely randomized design (CRD). Results of statistical analysis on each parameter gives the following conclusion: The addition of yeast tempeh provide highly significant effect (P> 0.01) the protein content, moisture content, froth, southwest coagulation, pH, organoleptic color. Long fermentation gives highly significant effect (P> 0.01) the protein content, moisture content, froth, southwest coagulation, pH, organoleptic color. Interaction treatment had no significant effect (P <0.05) the protein content, moisture content, froth, southwest coagulation, pH, organoleptic color.Keywords: Quail eggs, yeast tempeh, fermentation and lactic acid.